AGILE SOFTWARE DEVELOPMENT ON DESIGN AND LAYOUT OF BOOKING ROOM WEBSITE (CASE STUDY: WITEL TELKOM YOGYAKARTA) - Reva Rahardian; Ananda Aulia Rizky; Narantyo Maulana Adhi Nugraha; Faisal Dharma Adhinata; Annisaa Utami (Jurnal Teknik Informatika (Jutif), 2022)
Online booking is one way to find and order easily using media connected using the internet network so that it can be accessed anywhere and anytime easily so that it can increase time effectiveness. One of the applications is Telkom Room which functions to help Telkom employees to book meeting rooms online to make them easier to use and don't need to come to the office and contact them to use them. The Booking Room website also uses the agile development method because the software development process requires a relatively short period and does not require enormous resources. Therefore, changes can be handled more quickly according to client needs and provide feedback to the development team in the manufacturing process. The existence of this Booking Room website can help facilitate the user in the room booking process so that the user does not have to come directly to the office and so that it is fast and easy to carry out the meeting process that will be held.